ANALISIS CLUSTERING DENGAN K-MEANS UNTUK PENGELOMPOKKAN PENJUALAN ELEKTRONIK PADA BATAM IT MART - Andrianto, Andrianto; Elisa, Erlin (Computer Science and Industrial Engineering, 2023)
This study aims to help Batam IT Mart in the process of grouping sales, and to find out data on the types of goods that are in demand and not in demand, with that sales data obtained by the store can be processed into useful information in the future. The method used in this research is the K-means Clustering which is done by grouping data into several groups and then carrying out a calculation process to get results in the form of groups of data on the types of goods that are very hot-selling, best-selling, and not-selling. The data used in this research is electronic sales data at Batam IT Mart from March 2019 to November 2022. The research has resulting 3 clusters such as cluster 0 that contained 19 items, cluster 1 that contained 2 items and cluster 2 that contained 4 items. So the conclusion drawn is the analysis and grouping using k-means clustering method can help in doing the segmentation and grouping of the sales data. From this research, it is obtained renewal in the form of a cluster that can assist in analyzing and providing segments for goods sold at Batam IT Mart.